Isolation and Genetic Characterization of Canine Parvovirus in a Malayan Tiger - Nur-Farahiyah, Ahmad Nadzri; Kumar, Kiven; Yasmin, Abd Rahaman; Omar, Abdul Rahman; Camalxaman, Siti Nazrina (Frontiers in Veterinary Science, 2021)
Naïve Felidae in the wild may harbour infectious viruses of importance due to cross-species transmission between the domesticated animals or human-wildlife contact. However, limited information is available on virus shedding or viraemia in the captive wild felids, especially in Malaysia. Four infectious viruses of cat: feline herpesvirus (FHV), feline calicivirus (FCV), canine distemper virus (CDV) and canine parvovirus (CPV), were screened in leopards, feral cats and tigers in Malaysia based on virus isolation in Crandell-Rees feline kidney (CRFK) cells, PCR/RT-PCR and whole-genome sequencing analysis of the positive isolate. From a total of 36 sera collected, 11 samples showed three consecutive cytopathic effects in the cell culture and were subjected to PCR using specific primers for FHV, FCV, CDV and CPV. Only one sample from a Malayan tiger was detected positive for CPV. The entire viral genome of CPV (UPM-CPV15/P. tigris jacksoni; GenBank Accession number MW380384) was amplified using the Sanger sequencing approach. Genome sequencing of the isolate revealed 99.13, 98.65 and 98.40%, close similarity with CPV-31, CPV-d Cornell #320 and CPV-15 strains, respectively and classified as CPV-2a. Time-scaled Bayesian Maximum Clade Credibility tree for the non-structural (NS) genes of CPV showed a close relationship to the isolates CPV-CN SD6_2014 and KSU7-SD_2004 from China and USA, respectively, while capsid gene showed same ancestor to FPV-BJ04 strain from China. Higher evolution rate of capsid protein (CP) (VP 1 and VP2) (1.649 x 10-5 (95% HPD: 7.626 X10-3 – 7.440 X10-3) as compared to NS gene (1.203 x 10-4 (95% HPD: 6.663 x 10-3 – 6.593 x 10-3) was observed in the CPV from this study, and fairly higher than other parvovirus species from Protoparvovirus genus. Genome sequencing of the isolated CPV from a Malayan tiger in the present study provides valuable information about the genomic characteristic of captive wild felids which may add information on the presence of CPV in species other than dogs.